Effect Of Use Of Flexible Transfemoral Prosthesis On Dynamic Balance Of Transfemoral Amputee - Nur Rachmat; Bambang Kuncoro (Jurnal Keterapian Fisik, 2022)
Background: The flexible transfemoral prosthesis is known to improve the level of independence in performing the daily activities of transfemoral amputees. Dynamic balance is needed by transfemoral amputee patients to be able to move properly. Methods: The research was conducted using a quasi-experimental research design with the post-test-only design method. A sample was obtained by the purposive sampling process. The Four Square Step Test (FSST) is used as an instrument to measure the dynamic balance. It was performed on 30 transfemoral amputee patients using axillary crutches, and then the patient wears a flexible prosthesis. The research was done at PT Kuspito Orthotic Prosthetics, and it was carried out from May to September 2022. Results: The research subjects were transfemoral amputee patients who met the inclusion and exclusion criteria determined by the researcher, a total of 30 patients. The subjects in this study were mostly male: 23 patients (76.67%). The largest proportions of respondents are aged 26–45 years (adults), as many as 17 people (56.675). The data normality test was obtained from dynamic balance using the four-square step IP-value of 0.07, which indicates that the data is normally distributed. With a significance of 0.000 and an average time to perform the four square step of 12.54 seconds versus 22.45 seconds with axillary crutches, patients walking with flexible artificial limbs had more stable balance than patients walking with axillary crutches. Conclusion: Patients with flexible artificial limbs are more balanced. It is recommended for transfemoral amputee patients to use a flexible prosthesis to improve dynamic balance when walking, so they can move better.